“Past fearing death”: Epicurean ethics in Measure for Measure - Jonathan Pollock (Sillages Critiques, 2013)
The numerous allusions to Montaigne’s Essays and Lucretius’ De rerum natura, especially in Act III of Measure for Measure, suggest that non only an “evangelical” but an Epicurean reading of the play is possible, according to which the Duke is not so much a divine figure as an atomist philosopher, advocating measure (and pleasure) in all things.